Strategies of GIS-Based Urban Country Park Planning and Ecological Restoration - Li Hong; Songling Pang; Chunfu Zhu; Yuhao Li; Yuxiao Guo; Tingting Lei; Kun Wang (Discrete Dynamics in Nature and Society)
Purpose. This study centers around the Wangzhanghe Country Park located in Jiaozuo City as the research object. Through analysis of the site’s evolution by GPS and its status-quo by GIS, the map of spatial distribution suitability has been illustrated. Design. Based on the major principle of achieving sustainable development of the ecosystem and the derived concept of building a diversified landscape, we have developed the overall scheme of planning and landscape layout of the country park. Specifically, the area of ecological restoration is further divided into the areas of quarry restoration, bare land restoration, slope protection, vegetation, and dam maintenance, and restorative measures are put forward accordingly. Findings. Our research findings indicate that thanks to the vegetation restoration of the side slope, the area of bare land in mountain farmland has been evidently reduced, whereas the severely damaged ash pits and green spots have also been restored. Originality: in the meantime, we have leveraged the flat space at the foot of the mountain to foster a viewing experience and provide recreational activities for citizens, so that they are able to effectively increase their access to outdoor events and improve their sense of engagement and experience in the events, thereby providing a reference for building a green, diverse, and sustainable system of ecological services for the urban country park.